2012
DOI: 10.4028/www.scientific.net/amr.548.853
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of Solid-Liquid Two-Phase Turbulent Flows through Francis Turbine

Abstract: This work is to investigate solid-liquid flows inside entire passage of a large Francis turbine unit and a modified algebraic model is proposed to take the solid-phase turbulent viscosity into consideration based on realizable turbulence model for the liquid phase and further development of the commercial CFD software. The energy conversion between the pressure and velocity, and the sedimentation distribution characteristics around all the hydraulic parts are simulated. The calculated velocity and sedimentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…It has been found that the erosion process is strongly dependent on the operating conditions of the turbines. Tang et al 19 conducted secondary development to CFD and studied the solid-liquid two-phase flow in a Francis turbine by using the modified algebraic model, and the simulation results are consistent with the actual project. Thapa et al 20,21 optimized the turbine in sandy water through numerical simulation and experimental study, effectively reduced the sand erosion, and improved the turbine efficiency.…”
Section: Introductionmentioning
confidence: 79%
“…It has been found that the erosion process is strongly dependent on the operating conditions of the turbines. Tang et al 19 conducted secondary development to CFD and studied the solid-liquid two-phase flow in a Francis turbine by using the modified algebraic model, and the simulation results are consistent with the actual project. Thapa et al 20,21 optimized the turbine in sandy water through numerical simulation and experimental study, effectively reduced the sand erosion, and improved the turbine efficiency.…”
Section: Introductionmentioning
confidence: 79%
“…The CFD software was used and secondly developed to simulate the solid-liquid two-phase flow in turbines. Tang, et al conducted secondary development to CFD, and studied the solid-liquid two-phase flow in a Francis turbine by using the improved algebraic model, and the simulated results are consistent with the actual project [13]. The joint effect of sand wear and cavitation to the erosion of turbine components was studied.…”
Section: Introductionmentioning
confidence: 98%
“…At present, some progress has been made in numerical simulation of centrifugal pump flow performance [25][26][27][28][29][30][31][32][33][34][35][36]. However, the overall flow performance of the centrifugal pump, especially the two-phase flow performance under the condition of high concentration of fine particles, is not sufficiently studied due to the complexity of solid-liquid two-phase flow in the pump.…”
Section: Introductionmentioning
confidence: 99%